EFEKTIVITAS PENEGAKAN HUKUM DI BIDANG KEKAYAAN INTELEKTUAL OLEH PENYIDIK PEGAWAI NEGERI SIPIL - Harison Citrawan; Achmad Fikri Rasyidi (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2019)
AbstractThis study attempts to analyse the effectiveness of intellectual property law enforcement by civil servant investigator. By applying the psychological type of the cognitive function, this study finds that: first, internally the civil servant investigator has in principal conducted their normative duties, although it yet to be ideal. Several internal factors that affect such a situation covering: (i) there is yet an organizing structure of IP investigator at the Law and Human Rights Regional Offices; and (ii) mismanagement in managing and positioning the investigators, as some are currently working in units outside the investigations duty. Second, externally based on normative review, it could be understood that IP law enforcement could be pursued through various mechanisms. In this context, the law has yet to endow the civil servant investigator an authority to get involved in penal mediation, which by and large delimits their ability in enforcing the law. IntisariKajian ini mencoba menggambarkan efektivitas penegakan hukum oleh PPNS di bidang kekayaan intelektual (KI). Dengan menggunakan psychological type of the cognitive function, ditemukan bahwa: Pertama, secara internal PPNS KI  (KI) sudah menjalankan tugas dan fungsi PPNS KI, meskipun belum pada level ideal. Faktor-faktor internal yang memengaruhi hal tersebut yakni: (i) belum terdapat struktur PPNS KI di Kantor Wilayah Hukum dan HAM, dan (ii) penempatan PPNS ke dalam jabatan atau posisi tertentu yang tidak relevan dengan tugas dan wewenang PPNS. Kedua, secara eksternal berdasarkan tinjauan normatif, dipahami bahwa penegakan hukum KI dapat menempuh beberapa jalur. Adapun normativitas kewenangan PPNS yang tidak mencakup ranah mediasi penal justru menyebabkan kewenangan mereka menjadi sangat terbatas.